Proposed instructional materials in communication arts for grade II based on Individualized approach with notes for the teacher - Orola, Lilia Lopez 1947-
The study contains instructional materials based on the individualized instruction approach. Instructional materials designed and used by the Bureau of Public Schools were examined to determine the concepts and skills appropriate for the learning capacity of the grade II pupils. The main take and sub-tests for the grade were drawn. The tasks are pathways to the mastery of total task. Then the scope and sequence chart for each unit was prepared.